From Digitalization to Public Adoption: An Analysis of Innovation Diffusion of the AMAN Application in the Transformation of Public Services in Pekanbaru City - Eka Anjani Sapitri; Lolita Deby Mahendra Putri (Universitas Tribhuwana Tungga Dewi, 2026)
Quality public services are one of the indicators of successful government administration. Public service innovation represents a form of governance reform aimed at improving the effectiveness of service delivery. This study aims to analyze the implementation of public service innovation through the Multipurpose Safe and Comfortable Application (AMAN) managed by the Department of Communication, Informatics, Statistics, and Encryption of Pekanbaru City. This study employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The research informants consist of application managers and service users. Data analysis was conducted interactively through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the AMAN application innovation has not been fully optimal. Based on Rogers’ five diffusion of innovation indicators, the AMAN application demonstrates strengths in relative advantage through the integration of public services into a single digital platform and compatibility with the needs of Pekanbaru City residents. However, challenges remain in complexity due to limited integration among local government agencies, trialability due to insufficient public trials and socialization, and observability because some services remain inaccessible to users. Strengthening coordination, institutional capacity, and stakeholder collaboration is required to support the sustainability of this innovation.Pelayanan publik yang berkualitas menjadi salah satu indikator keberhasilan penyelenggaraan pemerintahan. Inovasi pelayanan publik merupakan bentuk pembaruan dalam tata kelola pemerintahan yang bertujuan meningkatkan efektivitas penyelenggaraan layanan. Penelitian ini bertujuan menganalisis pelaksanaan inovasi pelayanan publik melalui aplikasi Multipelayanan Aman dan Nyaman (AMAN) pada Dinas Komunikasi, Informatika, Statistik, dan Persandian Kota Pekanbaru. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Informan penelitian terdiri atas pihak pengelola aplikasi dan masyarakat pengguna layanan. Analisis data dilakukan secara interaktif melalui tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi inovasi aplikasi AMAN belum sepenuhnya optimal. Berdasarkan lima indikator difusi inovasi Rogers, aplikasi AMAN telah menunjukkan keunggulan pada aspek keuntungan relatif (relative advantage) melalui integrasi layanan dalam satu platform digital serta aspek kesesuaian (compatibility) dengan kebutuhan masyarakat. Namun, masih terdapat kendala pada aspek kerumitan (complexity) akibat keterbatasan integrasi antarperangkat daerah, aspek kemungkinan dicoba (trialability) karena belum optimalnya uji coba dan sosialisasi, serta aspek kemudahan diamati (observability) karena sebagian layanan belum dapat diakses secara optimal. Penguatan koordinasi, kapasitas kelembagaan, dan kolaborasi antaraktor diperlukan untuk mendukung keberlanjutan inovasi.